Nursing management of oral rehydration therapy in pediatric patients with gastroenteritis and hypovolemia at a general hospital: A case study - Helda Apriliana; Fitri Afdhal; Muhammad Romadhon; Ria Wulandari (Lentera Perawat, 2025)
Background: Gastroenteritis is an inflammation of the stomach and small intestine caused by bacterial or viral infection, characterized by symptoms such as defecation more than three times per day. This condition often leads to nursing problems including impaired skin integrity, discomfort or pain, hyperthermia, and, most commonly, fluid volume deficit (hypovolemia). Oral rehydration therapy (ORT) plays an essential role in preventing hypovolemic complications, particularly dehydration ranging from mild to severe. ORT not only restores the balance of sodium and potassium concentrations in the body but also accelerates the recovery process. Objective: This study aimed to provide nursing care and to evaluate the effectiveness of oral rehydration therapy in children with gastroenteritis and hypovolemia in a general hospital. Methods: A case study approach was applied to explore nursing care management for pediatric patients with gastroenteritis and hypovolemia receiving oral rehydration therapy. The study compared two pediatric clients aged 1–5 years, admitted in July 2024 with gastroenteritis and hypovolemia. Data were collected through informed consent forms, interviews, observations, physical examinations, pediatric nursing assessment formats, and documentation. The case study was conducted over three consecutive days in a general hospital setting. Results: After three days of nursing interventions, with the primary diagnosis of hypovolemia related to active fluid loss, the administration of oral rehydration therapy demonstrated effective outcomes. Nursing care interventions— including observation, therapeutic actions, education, and collaboration—led to the resolution of the problem on the third day of care. Conclusion: This case study highlights the comparison of nursing care in two pediatric clients with gastroenteritis and hypovolemia undergoing oral rehydration therapy, showing that the intervention effectively resolved the problem within three days. Continued parental education was provided as part of the follow-up care.